PETUNJUK RASULULLAH SAW TENTANG KEUTAMAAN ORANG YANG BERILMU - Abdul Wahab Syakhrani; Khairun Nida; Niatu Jannah; Noerhasimah Noerhasimah; Norainah Norainah (ADIBA : JOURNAL OF EDUCATION, 2022)
Hadith Bukhari: 71 explains about the prohibition of envy because it is a disgraceful act, envy is allowed to two types of people, namely people who use their wealth in the way of truth and people who practice and teach wisdom to others, and envy here is positive envy, as a motivation us to be like them. Muslim Hadith: 1631 explains that knowledge is then practiced, then the reward will never be cut off. Everything in this world will end except for 3 things, namely: Alms Jariyah, useful knowledge, pious children. And those three things will continue to give endless rewards, even though we have died, even though we are gone. Hadith Bukhari: 100 explains that Allah does not kill servants or humans but Allah sends the scholars, people of knowledge who obey Allah, so that in this world there is nothing left, only stupid people on earth and he also became a leader so that he gave a fatwa with his own fatwa so that people became misguided.